1985
DOI: 10.1136/oem.42.6.380
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic potential of hydrotreated petroleum aromatic extracts.

Abstract: Five experimental petroleum extracts were produced from luboil distillates derived from Middle East paraffinic crude by solvent extraction and severe hydrotreatment. The polycyclic aromatic content (PCA) of the extracts was determined by dimethyl sulphoxide extraction and ranged from 3.7-9.2% w/w. The five extracts were evaluated for their potential to induce cutaneous and systemic neoplasia in female mice derived from Carworth Farm No 1 strain (CF1). The test substances were applied undiluted (0.2 ml per appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…HRBO and OLBO are commonly known as "mineral oils". Test materials were applied undiluted in a defined volume to the shaved backs of the animals 1-3 times per week (Doak et al 1983;Blackburn et al 1984;Doak et al 1985;Blackburn et al 1986;Roy et al 1988;McKee, Daughtrey, et al 1989;McKee, Nicolich, et al 1990;Chasey and McKee 1993;Concawe 1994). In some cases, test materials were diluted in highly refined mineral oil or toluene for reasons of high toxicity or high viscosity (Blackburn et al 1986;McKee, Daughtrey, et al 1989;McKee, Nicolich, et al 1990).…”
Section: Carcinogenicity Of Pahs and Moahmentioning
confidence: 99%
See 1 more Smart Citation
“…HRBO and OLBO are commonly known as "mineral oils". Test materials were applied undiluted in a defined volume to the shaved backs of the animals 1-3 times per week (Doak et al 1983;Blackburn et al 1984;Doak et al 1985;Blackburn et al 1986;Roy et al 1988;McKee, Daughtrey, et al 1989;McKee, Nicolich, et al 1990;Chasey and McKee 1993;Concawe 1994). In some cases, test materials were diluted in highly refined mineral oil or toluene for reasons of high toxicity or high viscosity (Blackburn et al 1986;McKee, Daughtrey, et al 1989;McKee, Nicolich, et al 1990).…”
Section: Carcinogenicity Of Pahs and Moahmentioning
confidence: 99%
“…Only some studies reported the size of the dermal treatment area (McKee, Daughtrey, et al 1989;Chasey and McKee 1993). White mineral oil and toluene were reported to be used as negative/ vehicle controls, and B[a]P (in toluene or acetone) and catalytically cracked clarified oil as positive controls (Doak et al 1985;Blackburn et al 1986;McKee, Daughtrey, et al 1989;McKee, Nicolich, et al 1990;). Shaved but untreated animals were reported to be used as additional negative controls (Doak et al 1985;Blackburn et al 1986;.…”
Section: Carcinogenicity Of Pahs and Moahmentioning
confidence: 99%
“…At the same time, epidemiological studies (Cruickshank and Squire, 1950;Cruickshank and Gourevitch, 1952;Waterhouse, 1971; and Thony and Thony, 1970) have linked exposure to unrefined oils to an excess incidence of skin cancer in humans. Chemical analysis of the carcinogenic oils showed that a portion of the carcinogenic activity can be attributed to the presence of polycyclic aromatic hydrocarbons (PAHs) (Bingham et al, 1965(Bingham et al, , 1969Grimmer et al, 1982;Gradisky et al, 1983;and Doak et al, 1985). This association has been supported by the observation that solvent refining, which quantitatively removes PAHs from oils, eliminates carcinogenic activity (Bingham and Horton, 1966;Doak et al, 1983;Halder et al, 1984;and Kane et al, 1984).…”
Section: Introductionmentioning
confidence: 69%
“…Therefore, DAEs are generally expected to contain relatively high amounts of PACs and to be carcinogenic. [12][13][14][15] Vacuum residues are much less carcinogenic than distillates, 16 and RAEs are less carcinogenic than DAEs. [12][13][14] The primary route of concern is dermal due to the high viscosity of AEs (limiting aerosolization) and the anticipated uses of these products in end uses in which dermal exposure is the most likely route of exposure.…”
Section: Introductionmentioning
confidence: 99%